Factors influencing the success of an E-participation project in South Africa - Bennett, Dine (Department of Information Systems, 2015)
Dissatisfaction with service delivery is an enormous challenge for the current government of South Africa, as protests about service delivery are frequent and often violent and disruptive. E-participation could provide a means for dissatisfied citizens to voice their grievances, but it has not been duly exploited in South Africa. The purpose of this research is to contribute to knowledge of e-participation in developing countries , and specifically to identify the factors that influence the success of service delivery e-participation initiatives. A case study was conducted of an e- participation project - Project Lungisa - and qualitative data, in the form of interviews, documents and field notes, was collected and analysed in order to identify these influencing factors. As predicted in the literature review, citizens’ trust in government, stakeholder management, ICT infrastructure and project leadership were factors that influenced Lungisa’s success. Political consensus and inclusion did not influence success, and as a result two of the study ’s propositions could not be confirmed. Unanticipated factors that emerged as influential include local government support, independence from government and political parties, the use of mobile phone technology, marketing and advertising and community integration. A revised conceptual model is presented in the conclusion of this study, which could be tested in future research. Recommendations for practitioners are also given based on the nine influencing factors, and it is hoped that these will be of value to implementers of future e-participation projects.